A framework for evaluating the accessibility of raw materials from end-of-life products and the Earth's crust. (October 2017) - Mueller, Sandra R.; Wäger, Patrick A.; Turner, David A.; Shaw, Peter J.; Williams, Ian D.
Graphical abstract: Highlights: Defined and conceptualised raw material accessibility. Applied concept extraction in raw material management. Developed a framework for evaluating raw material accessibility. Carried out an evaluation with End-of-Life products and natural deposits. Developed an early project stage evaluation for accessing raw materials. Abstract: An increasing number of geochemically scarce metallic raw materials are entering into our lives via new technologies. A reversal of this trend is not foreseeable, leading to concerns regarding the security of their supply. However, the evaluation of raw material supply is currently hampered by inconsistent use of fundamental terminologies and incomplete assessment criteria. In this paper, we aim to establish a consistent framework for evaluating raw material supply from both anthropogenic and geological sources. A method for concept extraction was applied to evaluate systematically the use of fundamental terms in the evaluation of raw material supply. The results have shown that 'availability' is commonly used in raw material supply evaluations, whilst other researchers suggest that raw material supply should be evaluated based on 'accessibility'. It was revealed that 'accessibility' actually comprises two aspects: 'availability' and 'approachability'. Raw material 'approachability' has not previously been explicitly addressed at a system level. A novel, consistent framework for evaluating raw material supply was therefore developed. To demonstrate the application of the established framework, we evaluated the raw material supply of four rare earth element case studies. Three case studies are End-of-Life products (the anthroposphere) from Switzerland: (i) phosphors in fluorescent lamps, (i) permanent magnets in the drive motors of electric cars and (iii) fibre optic cable. The fourth case study source is the Earth's crust (the geosphere): Mount Weld deposit in Australia. The framework comprises a comprehensive evaluation of six components relating to raw material mining and processing: their geological knowledge, eligibility, technology, economic, societal and environmental impacts. Our results show that metals are not considered to be fully accessible in any of the case studies due to a lack of necessary technologies and potential societal and environmental impacts. The framework presented here can serve as a starting point for the development of an evaluation framework for raw material accessibility at an early project development stage.